2010
DOI: 10.1007/s11434-010-4015-5
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical estimation of Hammett σ p constants of organic radical groups

Abstract: A quantum chemistry method was developed to calculate the Hammett substituent constants of various organic radicals. These newly obtained constants allow, for the first time, the quantitative analysis of the electron demand of organic radicals. Calculations reveal that the electron demand of organic radicals varies dramatically. It was demonstrated that the Hammett relationship of bond dissociation energies is determined only by the change of electron demand during the homolysis process. organic radicals, homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Therefore, the effect of EWS or EDS on stabilization of a radical species (the product, intermediate, or transition state) is different from what is seen for an ion. This results in different Hammett constants for EWS and EDS on a radical (Wang et al 2010).…”
Section: Electronic Effect and Activitymentioning
confidence: 99%
“…Therefore, the effect of EWS or EDS on stabilization of a radical species (the product, intermediate, or transition state) is different from what is seen for an ion. This results in different Hammett constants for EWS and EDS on a radical (Wang et al 2010).…”
Section: Electronic Effect and Activitymentioning
confidence: 99%
“…As illustrated in Fig. 6G, a nearly linear correlation (reaction constant ρ = 1.08) implies that a process of negative charge accumulation may be involved in the rate-determining step ( 62 64 ). This experimental result is also in consistent with the deprotonation event of thioanisole radical cation proposed by an SET/proton transfer (SET/PT) mechanism.…”
Section: Resultsmentioning
confidence: 92%
“…It is well established that reactions involving para-substituted aromatic radicals have a complex linear free energy relationship due to the extra resonance stabilization felt at the para position . A study of the addition of free trichloromethyl radicals to substituted styrenes demonstrated that meta substituted styrenes fit a linear relationship with the σ + value while para-substituted styrenes did not .…”
Section: Introductionmentioning
confidence: 99%
“…17 It is well established that reactions involving para-substituted aromatic radicals have a complex linear free energy relationship due to the extra resonance stabilization felt at the para position. 19 A study of the addition of free trichloromethyl radicals to substituted styrenes demonstrated that meta substituted styrenes fit a linear relationship with the σ + value while para-substituted styrenes did not. 20 To deal with radical reactions, attempts have been made to determine a set of σ• constants for substituent effects on radical transition states (see Dust and Arnold 21 for a more extensive discussion).…”
Section: ■ Introductionmentioning
confidence: 99%